The Comparison of Appraisal Resources in Argumentative Essays Written by Students with Different Proficiency Levels - Fauziah, Meli; Warsono, Warsono; Widhiyanto, Widhiyanto (Universitas Negeri Semarang, 2019)
This study aimed to explain the appraisal resources manifested in argumentative essays written by undergraduate students with high and low proficiency level, as well as their similarities and differences of using appraisal resources. This study employed qualitative research in the form of written discourse analysis. The appraisal resources checklist adapted from Martin and White (2005) is used to determine the distribution of appraising items of attitude, engagement and graduation in argumentative essays written by high and low proficiency students. Out of 16 students chosen as the sample, 8 students are categorized as having high proficiency level, and the others eight belong to low proficiency level. The results of this study revealed that both groups of students utilized all subsystem of appraisal resources. However, high proficiency students dominantly used engagement rather than attitude and graduation. Meanwhile, the lows one utilized more attitude than engagement and graduation. In term of attitude, high proficiency students produced more appreciation. It showed that the argumentative essays written by high proficiency students are more appreciative than emotional and judgmental to align their personal voices in conveying their thoughts and opinions. In addition, in term of engagement, both groups dominantly applied entertain item in which it showed that both groups of students are successful to show their authorial voice towards the topic given. Finally, in graduation feature, force is dominantly used by both groups of students which means that they tried to intensify and quantify their arguments to build strong persuasion.